Student Critical Thinking Viewed from Mathematical Self-efficacy in Means Ends Analysis Learning with the Realistic Mathematics Education Approach - Taubah, Rofinda; Isnarto, Isnarto; Rochmad, Rochmad (Unnes Journal of Mathematics Education Research, 2018)
This research aimed to determine the effectiveness of learning by using the MEA model RME approach to the students’ critical thinking skills, and analyzedthe students’ critical thinking skills based on students’ mathematical self-efficacy.The research was conducted at SMP 1 Wedarijaksa, Pati, Central Java. Method used in this reaserch is mix method with concurrent embedded model. The sample in this research were the students ofVII I and VII C. Research findings showed learning by using the MEA model approach to the RME was effective to the students’ critical thinking skills. Critical thinking skills of mathematics towards mathematical self-efficacy, students with high mathematical self-efficacy were able to achieve the five aspects of critical thinking skills, namely drawing conclusions, assumptions, deductions, interpreting information and analyzing arguments. Students with mathematical self-efficacy have been able to achieve four aspects of critical thinking skills namely drawing conclusions, deductions, interpreting information and analyzing arguments. Students with low mathematical self-efficacy were only able to achieve two aspects of critical thinking skills, namely drawing conclusions and analyzing arguments.